ECONOMIC COOPERATION BETWEEN UZBEKISTAN AND CHINA WITHIN THE FRAMEWORK OF THE SHANGHAI COOPERATION ORGANIZATION (Conferencea, 2024)
The economic cooperation between Uzbekistan and China has significantly strengthened within the framework of the Shanghai Cooperation Organization (SCO). This paper examines the development, dynamics, and impact of this cooperation, highlighting key areas such as trade, investment, infrastructure development, and energy collaboration. The analysis focuses on the strategic initiatives and agreements facilitated by the SCO and the resultant economic benefits for both nations.